Fabrication and transport properties of thermally evaporated cadmium selenide thin films for photovoltaic applications. (2022) - Dhruv, D.K.; Dhruv, S.D.; Agrawal, Naveen; Patel, P.B.
Abstract: The present research article reports the fabrication and transport properties of Au/ n -CdTe Schottky diode prepared by the thermal evaporation technique. The microstructural examination of CdTe thin film was carried out using transmission electron microscopy (TEM). The diode was endangered to current ( I )-voltage ( V ) and capacitance ( C )-voltage ( V ) characterization using a computer-controlled semiconductor characterization system (SCS-4200) in dark surroundings. The activation and bandgap energies of n -CdTe were determined by plotting DC electrical resistance ( R ) variation with temperature ( T ). The I-V analysis of pristine Schottky diode showed rectifying behaviour, and the diode' possible conduction mechanisms were determined. The diode ideality factor, barrier height and carrier concentration were derived accordingly. A theoretical energy band diagram was constructed for the Au/ n -CdTe Schottky diode-based Anderson's model. The photovoltaic behaviour of the fabricated Schottky diode was investigated, and results are reported. The implications are discussed.